A pilotstudy on roles and operations of actors in the beef value chain in central and Western Uganda - Kyayesimira, Juliet; Rugunda, Grace Kagoro-; Lejju, Julius Bunny; Nalwanga, Rosemary; Matofari, Joseph W.; Andama, Morgan (International Journal of Development and Sustainability, 2018)
This study assessed the roles and operations of different actors in the beef value chain in the districts of Kiruhura, Mbarara, Kampala, Nakasongola and Nakaseke in Uganda. A total of 93 respondents were interviewed using a structured questionnaire. The findings revealed that men play a major role in the beef value chain with a few tasks limited to women. Beef traders make double profit during festive seasons compared to ordinary days. Live cattle are sold to the main urban towns in Uganda including Kampala(42.9%) and Mbarara (14.3%) among others as well as to South Sudan (14.3%) with Kiruhura (22.2%), Mbarara (15.9%) and Nakaseke (12.5%) districts being the leading suppliers. There was a significant (p<0.05) difference in prices of cattle categories. Cows cost higher (1,521,250 UGX) followed by mature bull (1,328,500 UGX), heifer (766,667UGX) and immature bull (668,750UGX). Some animal parts (bones, blood, claws, penis, brains) and intestinal ingesta are not utilized for economic gains. Live cattle trade should be abolished to realize more profits from beef sales and exports. Women should equally participate in the beef value chain. Different actors should be trained to add value on the unutilized animal parts and products to earn income. (Note: 1 USD=3693UGX)
Keywords: Farmers; Slaughter; Beef Traders; Transporters; Middlemen; Processers